Pearl Millet (Pennisetum glaucum [L. R. Rr.]) Varietal Loss and its Potential Impact on Smallholder Farmers in Northern Nigeria: A Review - Sa'adu Mafara Abubakar; Salisu Mohammed; Francis Bayo Lewu; Muhammad Nuraddeen Danjuma; Adetunji, Adewole Tomiwa; Kioko, Joseph I (Journal of Techno-Social, 2021)
Pearl millet is an alternative source of livelihood for poor farmers who use it to supplement food and income. Pearl millet has high medicinal value and its consumption reduce the risk of type 2 diabetes, constipation and anemia. Pearl millets is an excellent source of protein and fiber, and a great source of starch, making it a high-energy food. It is an exceptional food source for babies from six months of age because it has high nutrients and is easily digestible. Pearl millet is the most widely cultivated millet varieties in the world. The cereal crop is grown in arid, infertile, marginal lands in Africa and Asia, and cope with unpredictable climatic conditions. Nigeria is the second largest producer of pearl millet in the world with tremendous amount of pearl millet diversity. However, there is growing recognition that the diversity of pearl millet in northern Nigeria is vastly diminishing thereby affecting the livelihood of smallholder farmers. This paper reviews the erosion of pearl millet, multiple drivers of loss of local varieties of pearl millet, and presents some of the strategies that can be implemented to save the erosion of its diversity in northern Nigeria.